2018
DOI: 10.1136/postgradmedj-2017-135437
|View full text |Cite
|
Sign up to set email alerts
|

Surgical gender gap: a curriculum concordance and career vector perspective

Abstract: IntroductionWomen’s participation in medicine has increased dramatically during the last 50 years, yet Office for National Statistics data (2016) regarding annual pay continue to show an unequivocal 34% deficit in female doctors’ remuneration compared with their male counterparts. This study aimed to identify whether there are measurable differences in the training, career vectors and profiles of higher general surgical trainees (HSTs), related to gender.MethodThe Deanery roster supplemented with Intercollegia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Women spent significantly longer in training than men (median 85, range 71–141 vs 72, range 63–108 months, p=0.003), and male gender was associated with a higher number of total publications (8 vs 5.5, p=0.004) and first-author publications (4 vs 3, p=0.002). A subsequent study by Brown et al 12 reported that that women comprised some one-third of surgical trainees over the last decade and the attrition rates from the training programme were comparable. Yet, significant and complex variable gender divergences were apparent related to time in training, subspecialty career choice and academic profile, but not operative learning curve trajectory, arguably reflecting differences in social and cultural values, and resulting in a variance in professional credentials at CCT.…”
Section: Discussionmentioning
confidence: 98%
“…Women spent significantly longer in training than men (median 85, range 71–141 vs 72, range 63–108 months, p=0.003), and male gender was associated with a higher number of total publications (8 vs 5.5, p=0.004) and first-author publications (4 vs 3, p=0.002). A subsequent study by Brown et al 12 reported that that women comprised some one-third of surgical trainees over the last decade and the attrition rates from the training programme were comparable. Yet, significant and complex variable gender divergences were apparent related to time in training, subspecialty career choice and academic profile, but not operative learning curve trajectory, arguably reflecting differences in social and cultural values, and resulting in a variance in professional credentials at CCT.…”
Section: Discussionmentioning
confidence: 98%